The Management of Local Government Apparatus Resource Based on Job and Workload Analysis - Cahyasari, Erlita (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2016)
This Papers focus on job analysis as the basis of human resource system. It is describe about the job and workload and also the obstacles that are perhaps to observe during the work, and to supply all of activities of human resource management in the organization. Workload analysis is a process to decide the sum of time required to finish a specific job. The result of job and workload analysis goals to determine the number of employees needed in correspond to some specific workload and responsibilities given to an employee (the right man on the right place).